SERVER STATISTIKA JUMLAH JEMAAT GBKP KLASIS MENARA (MEDAN-NAMORAMBE) BERBASIS WEB - Atania Br Ketaren; Ertina Sabarita Barus (UPPM, 2020)
The internet can be used to facilitate all work effectively and efficiently. GBKP has data on the number of congregations who worship each week. This data can only be seen through congregational newspapers provided by the church. However, it is not yet possible to see the number of congregants that attend each Runggun in 1 classic. By utilizing the internet, viewing congregation's data will be easier and can be accessed anytime and anywhere. In this research, a server was created to view statistical data regarding the number of class-level congregations. The research purposes were to find out the number of congregants who attend Sunday services. This research, has a proposed design system including dfd, erd, flowchart and database (database). The statistical server design for the GBKP Klasis Menara congregation is expected to facilitate the process of inputting the number of congregations.